The Effects of Selenium Supplementation on the Spontaneously Occurring Fibroid Tumors of Oviduct, 8-Hydroxy-2?-Deoxyguanosine Levels, and Heat Shock Protein 70 Response in Japanese Quail - Tuzcu, Mehmet; Şahin, Nurhan; Ozercan, Ibrahim; Seren, Soley; Şahin, Kazım; Küçük, Ömer (Routledge Journals, Taylor & Francis Ltd, 2010)
Oxidative stress is known to be an important contributing factor in many chronic diseases. Spontaneously occurring benign oviduct leiomyomas are common tumors of the Japanese quail (Coturnix coturnix japonica), which makes it a good animal model for screening potential agents for testing in the prevention and treatment of human myoma uteri. Since dietary intake of selenium has been associated with a reduced risk of a variety of human cancers, we investigated the effects of selenium supplementation on the development of leiomyomas in the Japanese quail. Potential mechanisms of action of selenium include its antioxidant properties and modulation of heat shock protein 70 (Hsp70); therefore, we measured levels of 8-hydroxy-2'-deoxyguanosine (8-OHdG), 8-isoprostane levels, and Hsp70 expression in tissue specimens obtained from the quails. One hundred and eighty quails (8 mo old) were assigned to 3 treatment groups consisting of 60 birds in each group. Birds were fed either a basal diet containing 0.048 mg Se per kg or the basal diet supplemented with 0.2 mg or 0.4 mg of selenium (Selenomax, yeast-bound l-selenomethionine, 60%) per kg of diet. The animals were sacrificed after 250 days, and the tumors were identified. Selenium supplementation did not affect the number of leiomyomas as compared to control subjects (P > 0.05). However, the tumors in selenium fed birds were smaller than those found in control birds (P = 0.01). Serum Se increased (P = 0.01), whereas MDA and 8-isoprostane, 8-OHdG concentrations decreased (P = 0.01) with selenium supplementation (P = 0.01). Selenium supplementation decreased Hsp70 in the tissue of birds. The results indicate that dietary supplementation with selenium reduces the size of spontaneously occurring leiomyoma of the oviduct in the Japanese quail.
Keywords: Heat-Shock Proteins; Lipid-Peroxidation; Ascorbic-Acid; Free-Radicals; Cancer; Hsp70; Inhibition; Expression; Prevention; Carcinoma